Membangun Narasi Akhlak dan Sejarah Islam Melalui Media Audiovisual Interaktif - Adrian Syaputra; Fhina Ardini; Neni Neni (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study discusses the development of narratives on Islamic morality and history through interactive audiovisual media as an effort to address the learning needs of the digital generation that demands high engagement, engaging visualizations, and immersive learning experiences. Based on library research methods, this study examines literature on narrative pedagogy, Islamic historiography, and digital learning technology to formulate a narrative model that integrates cognitive, affective, and interactive aspects. The review shows that although audiovisual media and technologies such as AR/VR have been proven to increase student motivation and understanding, studies specifically combining narratives on morality, Islamic history, and interactivity design are still limited. This study proposes a participatory narrative model based on interactive audiovisual through choice-based storytelling, reflective quizzes, and micro-scenarios that can strengthen historical understanding while internalizing moral values. The analysis shows that interactive media serves not only as a means of conveying information but also as a space for moral experience that allows students to build empathy, reflection, and value awareness. This study provides theoretical contributions to the development of narrative pedagogy in Islamic education and provides practical recommendations regarding media design, teacher readiness, and infrastructure support for the implementation of more effective and meaningful digital learning.